2019
DOI: 10.2308/jiar-17-561
|View full text |Cite
|
Sign up to set email alerts
|

Do Female Directors on Corporate Boards Make a Difference in Family Owned Businesses?

Abstract: This paper investigates how the presence of female directors on corporate boards impacts the performance of family firms. This study enriches the literature on gender diversity on corporate boards and its effects on firm performance by focusing on a country in which family businesses are dominant. The empirical analysis is conducted on a sample of 165 Italian-listed firms from 2011 to 2016, representing the period during which the mandatory gender quota law was introduced and implemented in Italy. The results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 66 publications
1
21
0
1
Order By: Relevance
“…Second, as prior studies have suggested that family firms may act differently than nonfamily firms with regard to board diversity and CSR practices, we distinguish between family and non-family firms by assessing directors' ownership as the ratio of equity held by family owners or promoters, which are board members to the total common stock (Magnanelli et al, 2020;Sahasranamam et al, 2019). Third, because results from Table 4 assert that the frequency of board meetings increases significantly firm's CSR score.…”
Section: Alternate Variables' Measuresmentioning
confidence: 99%
“…Second, as prior studies have suggested that family firms may act differently than nonfamily firms with regard to board diversity and CSR practices, we distinguish between family and non-family firms by assessing directors' ownership as the ratio of equity held by family owners or promoters, which are board members to the total common stock (Magnanelli et al, 2020;Sahasranamam et al, 2019). Third, because results from Table 4 assert that the frequency of board meetings increases significantly firm's CSR score.…”
Section: Alternate Variables' Measuresmentioning
confidence: 99%
“…It can be seen from Figure 6 that the proximity among "independence", "representation", "ethnic diversity", "impact", "finance", "investment", "size", and "women director" is high, suggesting that this set of keywords are used to describe recently emerging common research issues. Such research issues are associated with the relationship between the presence of women member/women director in the corporate board and the family firm performance (Arioglu, 2020;Bjuggren, Nordström, & Palmberg, 2018;González et al, 2020;Magnanelli et al, 2020).…”
Section: Conceptual Structurementioning
confidence: 99%
“…Similar to the former research direction, we also perceive the discordance among studies following this direction. On the one hand, the presence of women and the level of board diversity (measured by the percentage of women on the board) are found to be positively associated with the family firms' value and performance in developed countries, such as Italy (Magnanelli et al, 2020;, Portugal (Fėlix & David, 2019), and Turkey (Arioglu, 2020). On the other hand, studies in developing countries usually observe the adverse effects of female participation in the corporate board on family firms' performance (González et al, 2020;Mustafa, Saeed, Awais, & Aziz, 2020).…”
Section: Gender Diversity In the Family Business Corporate Boardmentioning
confidence: 99%
See 1 more Smart Citation
“…Raoli (2020) na Itália. Segundo as autoras, na Itália este número só começou a ganhar força quando da entrada em vigor de uma lei que obrigava as companhias abertas a manterem um número mínimo de 33% de mulheres nos três órgãos de conselho: de Endividamento de curto prazo, lucro líquido, lucro operacional e ativo total.…”
unclassified